Vocabulary research in 1983: A bibliometric analysis - Paul Meara (LingBaW)
This paper belongs to a series of studies devoted to L2 vocabulary research which has been published in the last fifty years. It follows on directly from my earlier analysis of the 1982 data, and attempts to broaden the base line on which the later research developed. The paper presents a brief bibliometric analysis of L2 vocabulary research published in 1983. The analysis identifies a number of research clusters that were not present in the 1982 research but will become significant in later years, and highlights the volatility of vocabulary research at this time.